Avaliação pontual da qualidade de antimaláricos no Sistema Único de Saúde - SUS - Fernando Henrique Andrade Nogueira (2007)
Malaria is the most devastating parasitic disease in the world, responsible for 300 to 500 million cases and 1 to 3 million deaths per year. The Brazilian Ministry of Health accounted for about 540 thousand cases in 2006. Among the greatest problems related to malaria therapy are the limited therapeutic arsenal and the plasmodium resistance to antimalarials. Antimalarial resistance can be triggered by many factors, including the use of substandard and/or counterfeit drugs. Drug quality must be continuously evaluated, mainly in tropical regions such as the Brazillian Amazon and other similarly endemic malarial regions. Three states in the North region of Brazil were selected for this antimalarial drug quality evaluation (the state storeroom and two localities in each state). Results were compared to those presented by CENADI (Central Nacional de Armazenamento e Distribuição de Insumos), located in Rio de Janeiro (non-endemic area). These locations have been visited and photographed, in order to assess drug storage conditions. Samples containing chloroquine phosphate, mefloquine hydrochloride, primaquine phosphate and quinine sulfate in the form of tablets were submitted to ambient conditions in those places for five months. Thereafter, they were collected and evaltuated by the Quality Control Laboratory for physical-chemical analysis. All samples were assayed according to United States Pharmacopeia 28nd edition and methods from scientific literature. Drug storage conditions were found inappropriate and needed improvements. Only one state storeroom showed adequate storage conditions, however samples were not evaluated due to misplacement. The remaining state storerooms and localities presented several improperties which can affect drug quality. Chloroquine samples showed no quality problems. Primaquine and quinine samples were found with manufacturing problems such as bad weight variation and packaging, not related to heat and humitidy. Release of mefloquine from tablets from CENADI location showed statistically significant difference with those stored in the North region, due to formulation problems or bad storage conditions. A method to assay mefloquine hydrochloride in tablets using high performance liquid chromatography was developed and validated in this work. Optimal chromatographic conditions were: methanol:monobasic potassium phosphate (0,05 mol/l) (60:40), flow rate 1 ml/min, C18 column 250 x 4,6 mm 5 ìm, injection volume 20 ìl, detection 283 nm. It showed selectivity to degradation products (hydrolisis and photolysis) and to substances structurally related to mefloquine hydrochloride. Linearity was demonstrated in the range 50 150 ìg/ml (R2 > 0,99), and also accuracy (98.81 100.25%) and precision (RSD of 0.84%).Detection limit and quantitation limit were 0.3 ìg/ml and 0.45 ìg/ml, respectively. The results remained unaffected by modifications in the mobile phase composition (±3%), flow rate (± 0,1 ml/min) and temperature (± 5oC), but not to changes in the buffer pH (± 0,5). Keywords: Antimalarial; quality control; stability